Polymorphisms of genes in neurotransmitter systems were associated with alcohol use disorders in a Tibetan population. - Yan Xu; Wan-Jun Guo; Qiang Wang; Gongga Lanzi; Ouzhu Luobu; Xiao-Hong Ma; Ying-Cheng Wang; Puo Zhen; Wei Deng; Xiang Liu; Basang Zhuoma; Xie-He Liu; et al. (PLoS ONE, 2013)
Studies of linkage and association in various ethnic populations have revealed many predisposing genes of multiple neurotransmitter systems for alcohol use disorders (AUD). However, evidence often is contradictory regarding the contribution of most candidate genes to the susceptibility of AUD. We, therefore, performed a case-control study to investigate the possible associations of genes selected from multiple neurotransmitter systems with AUD in a homogeneous Tibetan community population in China. AUD cases (N = 281) with an alcohol use disorder identification test (AUDIT) score ≥10, as well as healthy controls (N = 277) with an AUDIT score ≤5, were recruited. All participants were genotyped for 366 single nucleotide polymorphisms (SNPs) of 34 genes selected from those involved in neurotransmitter systems. Association analyses were performed using PLINK version 1.07 software. Allelic analyses before adjustment for multiple tests showed that 15 polymorphisms within seven genes were associated with AUD (p<0.05). After adjustment for the number of SNPs genotyped within each gene, only the association of a single marker (rs10044881) in HTR4 remained statistically significant. Haplotype analysis for two SNPs in HTR4 (rs17777298 and rs10044881) showed that the haplotype AG was significantly associated with the protective effect for AUD. In conclusion, the present study discovered that the HTR4 gene may play a marked role in the pathogenesis of AUD. In addition, this Tibetan population sample marginally replicated previous evidence regarding the associations of six genes in AUD.